An alternative approach to wound healing field; New composite films from natural polymers for Mupirocin dermal delivery - Okur, Neslihan Üstündağ; Hökenek, Nesrin; Okur, Mehmet Evren; Ayla, Şule; Yoltaş, Ayşegül; Siafaka, Panoraia I.; Cevher, Erdal (Elsevier, 2019)
In this study, novel adhesive films were prepared for Mupirocin dermal delivery. Natural polymers as chitosan, sodium alginate and carbopol were used for films development to evaluate possible interactions and drug release properties. Solvent evaporation method was used for films preparation. Preliminary studies involved FT-IR spectroscopy and Scanning Electron Microscopy to specify interactions and morphology. Thickness, tensile strength and water uptake in phosphate buffer saline were evaluated whereas in vitro release studies were also performed. In vitro drug release studies demonstrated that mupirocin release was improved. Ex vivo bioadhesion and permeation studies using Balb-c mice were performed to check the suitability of the films. Antimicrobial ability was evaluated by agar well diffusion tests. Finally, excisional wound model applied to test the wound healing effect and evaluated macroscopic and histopathologically. One formulation was found more effective compared to the market product for wound healing at Balb-c mice.
Keywords: Chitosan; Sodium Alginate; Mupirocin; Dermal Delivery; Wound Healing; In Vivo